2007
DOI: 10.1152/ajpendo.00526.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose feeding during pregnancy and lactation elicits distinct metabolic response in offspring of an inbred genetic model of metabolic syndrome

Abstract: -The importance of early environment, including maternal diet during pregnancy, is suspected to play a major role in pathogenesis of metabolic syndrome and related conditions. One of the proposed mechanisms is a mismatch between the prenatal and postnatal environments, leading to misprogramming of the metabolic and signaling pathways of the developing fetus. We assessed whether the exposure to high-sucrose diet (HSD) alleviates the detrimental effects of sucrose feeding in later life (predictive adaptive hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 46 publications
2
20
1
Order By: Relevance
“…In contrast, the present study which investigated the effect of a maternal high sucrose diet during both prepregnancy through to suckling is arguably more relevant to the human situation. Recently, similar comparison was made in rats (Sedova et al, 2007). A high sucrose diet (70% calories as sucrose) was provided to inbred PD/Cub rats, which display a metabolic syndrome like phenotype, one week before breeding, and throughout pregnancy and suckling (Sedova et al, 2007).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In contrast, the present study which investigated the effect of a maternal high sucrose diet during both prepregnancy through to suckling is arguably more relevant to the human situation. Recently, similar comparison was made in rats (Sedova et al, 2007). A high sucrose diet (70% calories as sucrose) was provided to inbred PD/Cub rats, which display a metabolic syndrome like phenotype, one week before breeding, and throughout pregnancy and suckling (Sedova et al, 2007).…”
Section: Discussionsupporting
confidence: 62%
“…Recently, similar comparison was made in rats (Sedova et al, 2007). A high sucrose diet (70% calories as sucrose) was provided to inbred PD/Cub rats, which display a metabolic syndrome like phenotype, one week before breeding, and throughout pregnancy and suckling (Sedova et al, 2007). Contrary to our observations, this study revealed no increase in maternal weight gain or food intake in SF dams compared with control dams.…”
Section: Discussionsupporting
confidence: 62%
“…It was shown in humans that maternal high glycemic index of the diet during pregnancy was related to HOMA-IR, insulin, and leptin levels in the progeny at the age of 20 years 102. In an animal model, excessive maternal intake of sucrose resulted in higher adiposity, increased hepatic TG content, and elevated serum low-density lipoprotein cholesterol levels in the offspring 103. Intrauterine exposure to a fructose diet may, in turn, result in increased fasting insulin and elevated leptin and glucose levels in later life 95.…”
Section: Maternal Overweight and Diabetesmentioning
confidence: 99%
“…Excess energy intake during pregnancy results in programming of adverse metabolic outcomes in offspring such as obesity and diabetes in adulthood (Sedova et al, 2007). Both chronic hyperglycemia and insulin resistance may trigger neuronal death through oxidative stress and affect cognitive processes (Trevino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%